A three-stage criterion to reveal the bolt self-loosening mechanism under random vibration by strain detection. (March 2022) - Du, Jiangong; Qiu, Yuanying; Wang, Zhaoqian; Li, Jing; Wang, Haidong; Wang, Zhaoxi; Zhang, Jianyu
Highlights: A bolt loosening mechanism is revealed under random vibration by strain detection. A three-stage criterion to judge bolt loosening under random vibration is proposed. Bolt loosening comparison is made under triaxial and uniaxial random vibrations. Abstract: To study the self-loosening mechanism of fastening bolts, the triaxial random vibration environment test for a print circuit board is carried out with the triaxial vibrostand, and the simulation of the self-loosening process of bolts under the same vibration environment is made by the finite element method analysis, which obtains the curves of root mean square value of strain of monitored points varying with tightening torques. The strain curves obtained from the simulation have good consistency with both the test results and the fitted curves of the mode frequency differences, which effectively reveals the self-loosening mechanism of fastening bolts. Further the curves of the root mean square of strains respectively under the triaxial and uniaxial random vibrations are compared, and the difference between the curves reflecting their bolt self-loosening extents is found. Thus, a new method for determining the bolt self-loosening in the triaxial random vibration test by the root mean square of strains is proposed.